2005
DOI: 10.1128/aem.71.10.6165-6174.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cattle Feeding Regimen and Soil Management Type on the Fate of Escherichia coli O157:H7 and Salmonella enterica Serovar Typhimurium in Manure, Manure-Amended Soil, and Lettuce

Abstract: Survival of the green fluorescent protein-transformed human pathogens Escherichia coli O157:H7 and Salmonella enterica serovar Typhimurium was studied in a laboratory-simulated lettuce production chain. Dairy cows were fed three different roughage types: high-digestible grass silage plus maize silage (6:4), low-digestible grass silage, and straw. Each was adjusted with supplemental concentrates to high and low crude protein levels. The pathogens were added to manure, which was subsequently mixed (after 56 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
155
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(171 citation statements)
references
References 50 publications
8
155
2
1
Order By: Relevance
“…This suggested that the organism possibly uses combined mechanisms or even as-yet-unidentified alternative mechanisms. Strikingly, particular E. coli O157:H7 strains almost appeared as acidiphiles, as their survival was higher at low pH than at relatively high pH (Franz et al, 2005). However, a significant variation in the ability to survive in low-pH environments was found among isolates within a single serotype (Buchanan and Edelson, 1999).…”
Section: Phmentioning
confidence: 92%
See 2 more Smart Citations
“…This suggested that the organism possibly uses combined mechanisms or even as-yet-unidentified alternative mechanisms. Strikingly, particular E. coli O157:H7 strains almost appeared as acidiphiles, as their survival was higher at low pH than at relatively high pH (Franz et al, 2005). However, a significant variation in the ability to survive in low-pH environments was found among isolates within a single serotype (Buchanan and Edelson, 1999).…”
Section: Phmentioning
confidence: 92%
“…In an animal host body, temperature is often stable, whereas it may be strongly fluctuating in a non-host environment such as soil or water. Until recently, the effect of fluctuating temperature on E. coli survival and adaptation (compared with stable temperatures) in soil was poorly understood, as previous survival experiments had all been carried out under temperature-stable conditions (Kudva et al, 1998;Himathongkham et al, 1999;Franz et al, 2005). Recent results obtained with E. coli O157:H7 showed that survival in manure under fluctuating temperatures was generally lower than that under constant temperature (Semenov et al, 2007).…”
Section: Temperaturementioning
confidence: 97%
See 1 more Smart Citation
“…Microcosms were inoculated with the assemblages at similar final cell densities (OD 600 = 0.1). Thus, each microcosm received the species at a cell density of OD 600 = 0.1/s, where s is the number of species in the community inoculum (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). For microcosms containing strain T, the latter was introduced at OD 600 = 0.02, regardless of the established species richness.…”
Section: Methodsmentioning
confidence: 99%
“…The fate of the enterohemorrhagic Escherichia coli (EHEC) O157:H7 in soil is of major concern (18)(19)(20). In this context, the microbial communities that established after soil fumigation were shown to determine the fate of the invading species, whereby reduction in microbial diversity due to progressively enhanced fumigation depths resulted in higher pathogen persistence in soil (21).…”
mentioning
confidence: 99%